The Role of Advertising on Islamic Banks: An Evidence from Millennial Consumer’s Attitude and Intention - Faizi Faizi; Airlangga Surya Kusuma Kusuma (Jurnal Ilmiah Ekonomi Islam, 2023)
Since the establishment of Bank Syariah Indonesia as the largest Islamic bank in Indonesia, this bank has considered millennial consumers as its main potential customers. To gain these potential customers, Bank Syariah Indonesia launched a television advertisement for its product, namely Griya Simuda. The objective of this study is to investigate millennial consumers’ attitudes toward Griya Simuda television advertising and Griya Simuda product, and also millennial consumers’ intention to purchase Griya Simuda products. This research employs a quantitative approach, in which survey data from 155 millennial respondents were analyzed using simple linear regression analysis. The findings of this research showed that consumers’ attitude toward Griya Simuda advertising has a positive effect on consumers’ attitude toward Griya Simuda product. In turn, consumers’ attitude toward Griya Simuda product has a positive effect on the intention to purchase Griya Simuda product, and the attitude toward Griya Simuda advertising also has a positive effect on the intention to purchase Griya Simuda product. The conclusion of this research is that Islamic banks should utilize television advertisements more to promote their products.